MENJADI GURU: ANTARA REALITAS DAN IDEALITAS - Iskarim, Muchamad (IAIN Pekalongan, 2013)
Teacher is the centre of learning process and is also the centre of national education development. Without qualified teachers, the efforts to improve the quality of national resources and the competitiveness of the nation will be in vain. The quality of a good teacher is expected to be the goal of improving the quality of student learning. As it is explained in the Bill No. 14 of 2005 on Teachers and Lecturers, the quality of teachers is reflected in the mastery of competencies that must be owned. They are professional, pedagogical, personal, and social competence. Duties and responsibilities of teachers that are so heavy i.e. To educate national generation, brings about a logical consequence that the teachers should always attempt to improve their quality. Ironically, the teachers who are required to constantly improve their quality are not compensated by good salary. It makes their life far from prosperity. Many teachers do another work to meet their family’s needs. Although the government issued a policy of teacher certification, which is one of the agenda for their welfare, but it is not overcome the problem because there are still many problems in the implementation of the policy. Many of our teachers are still in the 'dilemma', on the one hand they have to improve their quality, but on the other hand he also have to consider their family’s needs.